Casting the customer: Persona and audience representation in local ads. case study: Beirut beer versus Almaza - Khoury, Josiane El (International Journal of Innovative Research and Scientific Studies, 2025)
Advertising, as part of Integrated Marketing Communications, is a crucial practice that connects the brand to its customers. When brands aim to reach their target audience effectively and try to retain customer loyalty, their advertisements need to reflect and mirror valuable aspects of the viewers. In the Lebanese context, many companies merge elements that resonate with their target audience or a category of people to try to strengthen their customer retention such as identification characteristics that might seem unnoticed to viewers. Beirut Beer, which directly competes with famous and similar companies in the Lebanese beer market, uses identification elements in its advertisements to try and resonate with a specific category of people that it aims to target and retain. This study analyzes and studies identification elements and practices that are included in Beirut Beer ads, examines why they were chosen, and how they affect the viewers’ choice in light of the VALS Theory, Identification Theory, and Persuasion Techniques. Our findings show that the identification elements used by Beirut Beer are chosen by taking into consideration their direct competitor and specifically choosing the opposite target audience. Therefore, instead of riskily trying to compete with older and more important companies in the Lebanese beer market and putting itself at risk, Beirut Beer’s main strategy is to target its competitor’s opposite audience.